Erratum: The Open Dentistry Journal, 2012, 6, 153-156 153-156 “Pyogenic Granuloma - Hyperplastic Lesion of the Gingiva: Case Reports” - Verma, Pushpendra Kumar * (Bentham Open, 2012)
Pyogenic granuloma is a reactive hyperplasia of connective tissue in response to local irritants. It is a tumourlike growth of the oral cavity, frequently located surrounding the anterior teeth or skin that is considered to be neoplastic in nature. It usually arises in response to various stimuli such as low-grade local irritation, traumatic injury, hormonal factors, or certain kinds of drugs. Histologically, the surface epithelium may be intact, or may show foci of ulcerations or even exhibiting hyperkeratosis. It overlies a mass of dense connective tissue composed of significant amounts of mature collagen. Gingiva is the most common site affected followed by buccal mucosa, tongue and lips. Pyogenic granuloma in general, does not occur when excised along with the base and its causative factors. This paper presents some cases of a pyogenic granuloma managed by surgical intervention.